Novel formation of Au/Ag bimetallic nanoparticles from a mixture of monometallic nanoparticles and their application for the rapid detection of lead in onion samples. (21st August 2020) - Sahu, Sushama; Sharma, Srishti; Ghosh, Kallol K.
Abstract : Characterization of gold, silver and gold/silver bimetallic nanoparticles for colorimetric detection of lead in onion samples. Abstract : The accumulation and contamination of heavy metals in vegetation are serious health threats to both humans and the ecosystem. One of the most common food ingredients, i.e ., onion, significantly uptakes the poisonous heavy metal lead (Pb) from soil. Herein, we report a facile synthesis of gold/silver (Au/Ag) bimetallic nanoparticles (BNPs) for colorimetric determination of Pb 2+ in onion ( Allium cepa L.) samples. The mechanism for the selective determination of Pb 2+ from sample solutions is confirmed by the red shift of the localized surface plasmon resonance (LSPR) band of BNPs in the visible region. The size, shape, composition and surface modification of BNPs are determined using UV-Vis spectroscopy, transmission electron microscopy (TEM), Fourier transform infra-red (FTIR) and energy dispersive X-ray (EDX) spectroscopies. The linear range for determination of Pb 2+ is 10–100 ng mL −1 with a detection limit and quantification limit of 5.28 and 17.62 ng mL −1, respectively. The good recovery percentage from 95.8 to 96.6% showed the selectivity method for Pb 2+ determination from complex sample matrices. The advantageous features of the proposed method are ease of operation, simplicity, selectivity and reproducibility for the determination of Pb 2+ in onion samples.